Teorisasi Dan Identitas Nalar Arab: Telaah atas Pemikiran Muhammad Abed Al-Jabiri - Pratama, Aunillah Reza (Universitas Islam Negeri Raden Intan Lampung, 2022)
Abstract;This research discusses Muhammad Abed Al-Jabiri's thoughts on the theory and identity of Arabic reason. Al-Jabiri, a prominent Moroccan philosopher and intellectual, offers an in-depth analysis of the history and structure of Arabic reason. Through his work, he explores how the Arab intellectual tradition developed and how the identity of that reason was shaped by the complex interaction between cultural, social, and political factors. This study focuses on the key concepts introduced by Al-Jabiri, such as “bayani reason,” “irfani reason,” and “burhani reason,” and how these concepts play a role in the formation and evolution of contemporary Arabic thought. Through a literature review, the study also highlights the relevance of Al-Jabiri's thought in the modern context and how this theorization can provide new insights into intellectual identity and dynamics in the Arab world.Keywords:Abed al-Jabiri; Arabic reasoning; Theorization. Abstrak;Penelitian ini membahas pemikiran Muhammad Abed Al-Jabiri tentang teori dan identitas nalar Arab. Al-Jabiri, seorang filsuf dan intelektual terkemuka dari Maroko, menawarkan analisis mendalam tentang sejarah dan struktur nalar Arab. Melalui karyanya, ia mengeksplorasi bagaimana tradisi intelektual Arab berkembang dan bagaimana identitas nalar tersebut dibentuk oleh interaksi kompleks antara faktor-faktor budaya, sosial, dan politik. Penelitian ini memfokuskan pada konsep-konsep utama yang diperkenalkan oleh Al-Jabiri, seperti